A Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry Direct-from-Urine-Specimen Diagnostic for Gram-Negative Pathogens - Hyojik Yang; Richard D. Smith; Kylie P. Sumner; David R. Goodlett; J. Kristie Johnson; Robert K. Ernst (Microbiology Spectrum, 2022)
ABSTRACT Urinary tract infections (UTIs) pose a major public health burden. The vast majority of UTIs are caused by Gram-negative bacteria. Current culture-based pathogen identification methods may require up to 24 to 48 h of incubation. In this study, we developed and evaluated a method for Gram-negative pathogen identification direct from urine, without culture, via matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) in approximately 1 h. Urine samples were collected (n = 137) from the University of Maryland Medical Center clinical microbiology laboratory. To identify bacteria direct from urine, two methods were evaluated. First, 1 μL of urine was directly spotted onto the MALDI target plate, and second, 1 mL of urine was centrifuged at 8,000 rpm for 5 min before processing using the fast lipid analysis technique (FLAT). Mass spectra were acquired on the Bruker MALDI Biotyper sirius system in the negative-ion mode. Results were compared to those of standard culture methods. When 1 μL of urine was directly spotted, positive agreement was 81.5% (101/124) and, after centrifugation, 94.4% (117/124) relative to that of standard culture methods. Negative agreement for both methods was 100% (13/13). The time to results for both of the specimen preparation methods using the FLAT extraction protocol was approximately 1 h, with minimal hands-on time required (<5 min). The ability to rapidly identify pathogens directly from urine, without the need for culture, allows for faster turnaround times and, potentially, improved patient outcomes. Overall, the FLAT extraction protocol, in combination with lipid A identification, provides a reproducible and accurate method to rapidly identify urinary pathogens. IMPORTANCE This study describes and evaluates a direct-from-urine extraction method that allows identification of Gram-negative bacteria via MALDI-TOF MS within 1 h. Currently, identification of urinary pathogens requires 24 h of culture prior to identification. While this method may not replace culture, we demonstrate its utility in screening for common urinary pathogens. By providing identifications in under 1 h, clinicians can potentially treat patients sooner with more-targeted antimicrobial therapy. In turn, earlier treatment can improve patient outcome and antimicrobial stewardship. Furthermore, MADLI-TOF MS is a readily available, easy-to-use diagnostic tool in clinical laboratories, making implementation of this method possible.